Metabolic and Endocrine Complications of Long-COVID-19: A Review - Bandara, Thushari; Deshmukh, Harshal A; Abdalla, Mohammed; Sathyapalan, Thozhukat (Experimental and Clinical Endocrinology & Diabetes, 2023)
Over the past two years, the outbreak of coronavirus disease of 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has centralized the interest of the health care systems and the scientific world. The majority of COVID-19-infected individuals recover fully. However, about 12–50% of patients experience various mid- and long-term effects after recovering from the initial illness. These mid- and long-term effects are collectively known as post-COVID-19 condition or 'long-COVID'. In the coming months, the long-term consequences of COVID-19 on the metabolic and endocrine systems may expect to rise and pose a global healthcare challenge. This review article discusses the possible metabolic and endocrine complications of long-COVID and the relevant research findings.
Keywords: long-COVID-19; chronic COVID; post COVID-19 syndrome; metabolic; endocrine; effects of long-COVID